Complex Dynamics of an Epidemic Model With Optimal Vaccination and Treatment in the Presence of Population Dispersal - Mandal, Manotosh; Jana, Soovoojeet; Nandi, Swapan Kumar; Kar, T. K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we describe an SEIR type epidemic model with a transport-related infection between two cities in the presence of vaccination and treatment control. The epidemiological threshold, commonly known as basic reproduction number is derived and its impact on the dynamical behaviour of the disease has been established. The optimal control problem is constructed with the objective of minimizing the effect of infection in the system and then it is solved. We compare the result of the model to a real-world problem to establish that our model can be used in some practical cases if the parameters are known.